Is there an association of blood cadmium level with nonmelanoma skin cancer: results from a cross-sectional study - Li, Dan; Chen, Jigang; Feng, Rui; Wang, Yanni (Frontiers in Public Health, 2025)
ObjectiveNonmelanoma skin cancer (NMSC) is a common malignancy that starts in the top layer of the skin. Exposure to heavy metals has been suggested to increase the risk of skin cancer. Cadmium, prevalent in various industries and present in cigarette smoke, has been implicated in potential skin effects in animal studies. However, the impact of chronic cadmium exposure on NMSC development remains largely unexplored. This study aimed to investigate the relationship between blood cadmium levels and the odds of NMSC.MethodsWe analyzed cross-sectional data from the National Health and Nutrition Examination Survey, covering the years 1999–2000 to 2017–2018. NMSC cases were identified through self-reported physician diagnoses. We assessed the association between blood cadmium levels—considered as both a continuous variable and in quartiles—and the odds of NMSC using multivariable logistic regression models. Restricted cubic splines (RCS) were incorporated to estimate the non-linear relationship between cadmium levels and NMSC.ResultsThe study included 41,577 participants, with 952 reporting NMSC and 40,625 without any cancers. No association was found between cadmium levels and NMSC when analyzed as either a continuous or quartile variable. However, RCS revealed an inverted U-shaped curve indicating a relationship between blood cadmium levels and NMSC odds. This pattern persisted when focusing exclusively on non-Hispanic White participants.ConclusionA statistically significant relationship was observed between blood cadmium levels and the odds of NMSC, though the increased odds were only evident at low cadmium levels. Further research is necessary to investigate the causality and underlying mechanisms involved.